Selektive Stimulation der verschiedenen Fotorezeptorklassen mittels Silent Substitution bei psychophysischen und elektroretinografischen Messungen - Huchzermeyer, Cord; Kremers, Jan (Klinische Monatsblätter für Augenheilkunde, 2022)
The silent substitution technique allows creating photoreceptor- selective stimuli for psychophysical and electrophysiological tests. In contrast to other techniques, the purpose of silent substitution is not to make the targeted photoreceptor type more sensitive in comparison to the other types, but to make the stimulus invisible ("silent") to the other photoreceptor types. This allows selectivity independent of the retinal state of adaptation and enables comparing photoreceptor types under identical conditions. The foundations of these techniques will be explained in this paper. Furthermore, the importance of postreceptoral processing for the perception of photoreceptor-selective stimuli is discussed here. Although this technique is currently only available in specialized vision science labs, there is an enormous potential for clinical application.
CRIS-Team Scopus Importer:2022-12-23
Keywords: electrophysiology; glaucoma; psychophysics; retina